Information architecture & mathematical modelling to optimally ‘fit’ human operator on motorcycle / Muhammad Izzat Nor Ma’arof - Nor Ma’arof, Muhammad Izzat (Institute of Graduate Studies, UiTM, 2015)
Code (2010) noted that motorcycles road accidents are always due to human error. Based on Stedmon (2010), it is strongly suggested that when the human operator’s working posture does not ‘fit’ the motorcycle, the human operator is prone to human error and possibly accident. Therefore, there is an existing link between motorcycle road accidents and motorcycle ergonomics. This study aimed to establish new motorcycle ergonomics information architecture from existing ergonomics knowledge for the establishment of new mathematical model to optimally ‘fit’ human operator on motorcycle. The motorcycle information architectures established were the Motorcycle Risk Information Architecture (MORIA) and Riding Posture Analysis Components (RIPAC) (consisting of RIPEC, HUMIS and RIPOC). Based on the MORIA, RIPAC, biomechanical analysis, and in referring to the guidelines provided by literature on physical loading and physiological stress, new mathematical model that proposed an optimally ‘fit’ riding posture for a human operator on motorcycle were established. The mathematical model is named the Bologna Triangle. In validating that the optimal ‘fit’ riding posture proposed by the Bologna Triangle is more advantageous; comparison were performed between the proposed riding posture, RIPOC riding postures and neutral sitting. The methods used in validating the Bologna Triangle were working posture ergonomics assessment, biomechanical analysis and experimental research design…